Politeness and Solidarity inOnline Apologies: A Sociolinguistic Comparison of Indonesian and American Political Leaders (2019-2025) - Ginting, Valencia Laurence; Sitorus, Rosalyn Magdalena; Fitriana, Fadila; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
National leaders' political apologies are essential for rebuilding public confidence, mending diplomatic relationships, and rewriting history. However, rigorous assessments of apologies made particularly by political leaders are still few, and the majority of extant literature concentrates on apologetic tactics in broad communication settings—such as interpersonal contacts, media discourse, or institutional pronouncements. Furthermore, there is a significant vacuum in the research since few studies examine how linguistic framing affects the perceived sincerity, responsibility, and political effect of these apologies across various national settings. By analyzing how political leaders create apologies through word selections, framing techniques, and rhetorical appeals, this study fills up these gaps. The study examines apology writings by various political personalities in response to historical injustices and national crises using a qualitative discourse-analytic method. The results highlight the intricate role of language in negotiating accountability during times of public scrutiny by showing how political apologies strategically combine responsibility-taking, emotional alignment, and future-oriented commitments to shape public perception and minimize political risk.